Secular Nationalism and Citizenship in Muslim Countries Arab Christians in the Levant (Minorities in West Asia and North Africa, 2018)
This edited volume examines the importance and significance of the Christian population in the Middle East and North Africa from the rise of Islam to present day. Specifically, the authors focus on the contributions of Christians to Arab politics, economy, and law. Using the current plight of Christians in the Muslim world (Iraq, Syria, Lebanon, Palestine, and Egypt), the contributors analyze the origins of the crises and propose recommendations and strategies to foster religious freedom, human rights, and an inclusive political system that ensures equality of citizenship for all communities to participate fully in their societies.